Aceh Government Policy in Preventing Radicalism Through the Existence of Dayah Islamic Education - W., Sulaiman; Lubis, Khairuddin; Baihaqi, M.; Musriaparto, Musriaparto; Marhaban, Marhaban; Nur, Muhammad (Nazhruna: Jurnal Pendidikan Islam, 2024)
This research aims to describe the Aceh government's policy in preventing radicalism through the existence of Dayah Islamic education. The pluralism of the Indonesian nation, including Aceh, the westernmost province of Indonesia, is one of the factors causing radicalism to quickly enter through global progress and the massive spread of Wahhabism, which can penetrate the gaps in Islamic education. Therefore, for prevention, the Aceh government implemented three essential policies. The results of field data from several key informants consisting of Aceh border Dayah leaders and the Aceh Dayah Education Service, which is strengthened by the results of field observations, lead to the conclusion that the success of the three Aceh government policies cannot be separated from the results of the peace negotiations between GAM (Free Aceh Movement) and Indonesia in 2005, which led to the issuance of the "Aceh Government Law" (UUPA), serving as the basis for the implementation of formal Dayah education in Aceh.